Uji Emisi Gas buang Pada Four Stroke Engine Menggunakan Multi-Feedstock Biodiesel Dengan Penambahan Zat Aditif (2-EHN) - Sa'diyah, Aminatus; Ardiansyah Lutfi, Dede; Haryono, Edi; Novianarenti, Eky; Rahmat Ramadani, Novan (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Perkapalan Negeri Surabaya, 2025)
The increase in gas emissions from fossil fuels, which contributes to the greenhouse gas (GHG) effect, not only impacts the environment but can also serve as an indicator of diesel engine performance. This situation has driven the development of environmentally friendly alternative fuels. This study aims to analyze the characteristics and exhaust gas emissions of multi-feedstock biodiesel fuels produced from palm oil, used cooking oil, and soybean oil, blended with Pertamina Dex, when used in a four-stroke diesel engine. The method employed is a laboratory experiment involving variations of B40 biodiesel blends, including B40 with the addition of 2-ethylhexyl nitrate (2-EHN) as an additive. The tests were conducted at engine speeds of 1000 RPM, 1200 RPM, and 1400 RPM, using a 4000-watt lamp as the load. The parameters evaluated include flash point, density, viscosity, cetane number, calorific value, and the emission levels of CO, NOx, and SO₂. The results indicated that the B40 fuel blend with the 2-EHN additive showed the best performance. This was reflected in improved fuel characteristics such as a cetane number exceeding 59.2, a reduced viscosity of 5.78 cSt, and lower CO emissions, with the highest value recorded at 84.89 mg/m³. Although NOx emissions slightly increased to 165.9 mg/m³, the value remains well below the standard exhaust emission limit of 3400 mg/m³.